Upregulating the positive affect system in anxiety and depression: Outcomes of a positive activity intervention. Issue 3 (6th January 2017) - Taylor, Charles T.; Lyubomirsky, Sonja; Stein, Murray B.
Abstract : Background: Research suggests that the positive affect system may be an important yet underexplored treatment target in anxiety and depression. Existing interventions primarily target the negative affect system, yielding modest effects on measures of positive emotions and associated outcomes (e.g., psychological well‐being). The objective of the present pilot study was to evaluate the efficacy of a new transdiagnostic positive activity intervention (PAI) for anxiety and depression. Method: Twenty‐nine treatment‐seeking individuals presenting with clinically impairing symptoms of anxiety and/or depression were randomly allocated to a 10‐session protocol comprised of PAIs previously shown in nonclinical samples to improve positive thinking, emotions, and behaviors (e.g., gratitude, acts of kindness, optimism; n = 16) or a waitlist (WL) condition ( n = 13). Participants were assessed at pre‐ and posttreatment, as well as 3‐ and 6‐month follow‐up, on measures of positive and negative affect, symptoms, and psychological well‐being. ClinicalTrials.gov Identifier: NCT02330627 Results: The PAI group displayed significantly larger improvements in positive affect and psychological well‐being from pre‐ to posttreatment compared to WL. Posttreatment and follow‐up scores in the PAI group were comparable to general population norms. The PAI regimen also resulted in significantly larger reductions in negative affect, as well as anxiety and depression symptoms, compared to WL. Improvements across all outcomes were large in magnitude and maintained over a 6‐month follow‐up period. Conclusions: Targeting the positive affect system through a multicomponent PAI regimen may be beneficial for generating improvements in positive emotions and well‐being, as well as reducing negative affect and symptoms, in individuals with clinically impairing anxiety or depression.